2018
DOI: 10.1108/mf-06-2017-0234
|View full text |Cite
|
Sign up to set email alerts
|

Teaching basic spreadsheet skills with peer tutoring

Abstract: Purpose Knowledge of spreadsheet tools like Microsoft Excel is a valuable skill to have in today’s job market. The preliminary assessment of a group of business school students shows that most of them struggle to perform simple tasks in a spreadsheet. The purpose of this paper is to propose using student tutors to teach these skills. Design/methodology/approach The authors identify students proficient in Excel as tutors and organize one-on-one peer tutoring lessons. The authors compare the Excel competency l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A good spreadsheet design will minimize or perhaps eliminate these errors [19]. Lipton et al [20] did a study on business school students by implementing a peer tutoring basic Excel knowledge to students with minimum skills and knowledge which struggles to perform even a simple task. Learning Excel is similar to learning a language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good spreadsheet design will minimize or perhaps eliminate these errors [19]. Lipton et al [20] did a study on business school students by implementing a peer tutoring basic Excel knowledge to students with minimum skills and knowledge which struggles to perform even a simple task. Learning Excel is similar to learning a language.…”
Section: Introductionmentioning
confidence: 99%
“…Learning Excel is similar to learning a language. Therefore, students can benefit from the personal tutoring sessions conducted [20].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, this result opposes the findings of Makgato (2014) where the majority of the teacher-respondents (21 out of 24 participants) indicated that they can use MS Excel spreadsheets. Nonetheless, Lantushenko, et. al (2018) emphasized that the knowledge of spreadsheet tools like Microsoft Excel is a valuable skill to have.…”
Section: Resultsmentioning
confidence: 99%
“…Payne and Tanner (2011) stress the need for finance students to apply statistical and computer analysis tools to the real world. Technical analysis in finance often relies heavily on using Microsoft Excel® (Lantushenko et al, 2018); our application allows the undergraduate analysts to apply their learned Excel skills and offers executive students the opportunity to observe, critique and learn about financial analysis in Excel. These tools enhance both graduate and undergraduate students' marketability and develop skills that can later be adapted for the workplace.…”
Section: Applications Of Experiential Learning In Financementioning
confidence: 99%